TURKEY'S AGRICULTURAL SECTOR IN GLOBAL COMPETITIVENESS ANALYSIS WITH INTERNATIONAL INDEX (Third Sector Social Economic Review, 2015)
If the agricultural sector between the relationship of other sectors considering in order to ensure the effectiveness and the growth of the agricultural sector must be efficient. A productive agricultural sector provide input to all sectors of the economy that search for are taking an active role in the development of industry and services. In the international arena increase the competitiveness of Turkey's agricultural sector and together with the rise this should be the primary goal of increasing export revenues obtained from the agricultural sector. This the target to see international arena in the agricultural sector see in 2014 the situation should determine what happens towards international competition. In this study was determined of the agricultural sector based on 2014 for the size of the global competitiveness the index were determined the size of the global competition.This size is moderate in international competition for our country. At the conclusion of the work to be done it is listed in general for further transportation of the agricultural sector.
Keywords: Agriculture Sector; Global Competition; International Trade